Flame-retardant polyamide composite material as well as preparation method and application thereof
By optimizing the composition of the flame-retardant polyamide composite material and adding a specific proportion of PA6I/6T and GMA grafted SEBS, the problem of difficult to take into account both the toughness and flame retardant properties of halogen-free flame retardant PA materials, and the material performance of high toughness and V-0 flame retardant is achieved.
Patent Information
- Application Number
- CN202411758315.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing halogen-free flame-retardant PA materials have low toughness, and when increasing toughness, the flame-retardant performance is easily degraded, making it difficult to meet the industry's dual requirements for high toughness and environmental protection.
The composition and processing process of the material are optimized to improve the flame retardant properties of the material and the impact strength of the cantilever beam notched by adding a specific proportion of crystalline polyamide, PA6I/6T, dialkylphosphate flame retardant, melamine derivative flame retardant and GMA grafted SEBS to the flame retardant polyamide composite material.
While maintaining the V-0 flame retardant performance, it significantly improves the impact strength of the cantilever beam notch of the material, and improves the overall performance of the halogen-free flame retardant PA material.
Smart Images

Figure SMS_1 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a flame retardant polyamide composite material and a preparation method and application thereof. Background Art
[0002] Flame-retardant nylon materials have good strength and toughness and are widely used in the field of electronics and electrical. Halogen-free flame-retardant reinforced PA has low smoke density, is halogen-free and has good environmental protection, and is increasingly used in the fields of electronics and electrical. However, halogen-free flame retardants are generally low-molecular substances in powder form, and the dispersion in PA resin is not very good. In addition, the addition amount is high, resulting in poor performance of the material, especially the toughness of the material, which is lower than that of halogenated materials. Generally, toughening agents are added to improve the toughness of materials, but in halogen-free systems, the addition of toughening agents has a significant negative impact on the flame retardancy of the material, resulting in the toughness of halogen-free materials not being effectively improved. With the improvement of the toughness and environmental protection requirements of materials in the industrial field, the demand for high-toughness halogen-free flame-retardant PA materials has become increasingly strong, and the development of high-toughness halogen-free flame-retardant PA materials is imminent.
[0003] At present, the toughness problem of halogen-free flame-retardant polyamide composites is mainly solved by the following two methods: First, using toughening agents, but conventional maleic anhydride grafted POE cannot solve the problem of decreased flame retardant properties of the material; second, by boiling in water, the water absorption rate of the halogen-free flame-retardant PA material is increased to improve the toughness of the material, but the processing steps are increased, which invisibly increases the material cost. Summary of the invention
[0004] The object of the present invention is to overcome the above technical defects and provide a flame retardant polyamide composite material having the advantages of V-0 flame retardancy and high Izod notched impact strength.
[0005] The present invention is achieved through the following technical solutions: A flame retardant polyamide composite material, comprising the following components in parts by weight: 20-35 parts of crystalline polyamide; PA6I / 6T 10-30 parts; 12-20 parts of dialkyl hypophosphite flame retardant; 1-5 parts of melamine derivative flame retardant; GMA grafted SEBS 0.5-2 parts.
[0006] The content of crystalline polyamide that can achieve the purpose of the present invention is 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 35 parts, etc. The content of PA6I / 6T is 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, etc. The content of dialkyl hypophosphite flame retardant is 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc. The content of melamine derivative flame retardant is 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc. The content of GMA grafted SEBS can be 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, etc.
[0007] The weight content of the crystalline polyamide in the flame-retardant polyamide composite material of the present invention is not less than 22wt%.
[0008] Preferably, in the PA6I / 6T, the mass ratio of isophthalic acid to terephthalic acid is (5-9):(5:1), preferably (6.5-7.5):(3.5-2.5).
[0009] PA6I / 6T can be a commercial product or can be obtained by self-production. The self-production method is as follows: a certain amount of terephthalic acid and hexamethylenediamine are mixed and 35-45% of deionized water is added, the molar ratio is 1:1.01~1.02, the temperature is adjusted to 45-55℃, the reaction is stirred for 1-3h, the pH value is adjusted to about 7.3~7.6, the reaction is continued for 1-3h, and a clear and transparent PA6T salt solution is obtained after the reaction is completed. After cooling, the solution is filtered and dried to obtain a white PA6T salt powder. The preparation process of PA6I salt is similar to the above steps. A fixed ratio of PA6I salt and PA6T salt are added to the reactor and mixed, and a certain amount of additives are added. After checking the air tightness, the mixture is replaced with nitrogen for more than 3 times, and the mixture is filled to a slight positive pressure of about 0.08-0.12 MPa. Stirring and heating are started, and the temperature is raised to 140-160℃ and the reaction is carried out for 1-3h, and then the temperature is continued to be raised to 200-220℃ and the temperature is maintained and the pressure is maintained for 3-6 h, the pressure is maintained at about 2.1-2.3 MPa, then the temperature is slowly raised to 300-320 ℃ within 2-4 h, and the pressure is gradually reduced to normal pressure. Finally, vacuum is applied, and the torque and current are observed. When the maximum value is reached, the stirring is stopped, nitrogen is filled in for back pressure, and the valve is opened to discharge the material to obtain PA6I / 6T product.
[0010] The crystalline polyamide is at least one of a polyamide resin obtained by polycondensation of a diamine and a dicarboxylic acid, a polyamide resin obtained by ring-opening polymerization of a lactam, a polyamide resin obtained by self-condensation of an aminocarboxylic acid, or a copolymer of the above polyamide resins.
[0011] Specifically, the polyamide resin obtained by polycondensation of diamine and dicarboxylic acid can be: PA66, PA56, PA46, PA610, PA612, PA1010, PA1212; The polyamide resin obtained by the ring-opening polymerization of lactam can be: PA6; The polyamide resin obtained by the self-condensation of aminocarboxylic acids may be: PA11, PA12; The copolymer of the above polyamide resin may be: copolymer PA66, copolymer PA6.
[0012] The present invention has no limitation on the intrinsic viscosity of polyamide, and the preferred intrinsic viscosity of polyamide is in the range of 2.3-2.7 dL / g. The intrinsic viscosity is tested according to ISO 307 test standard.
[0013] The structural formula of the dialkyl hypophosphite flame retardant is as follows: Among them, R 1 , R 2 Independently selected from linear or branched C1-C6 alkyl and / or aryl groups; M is selected from one or more combinations of alkali metals, alkaline earth metals, Al, Zn, Fe or Ti; m is 1-4.
[0014] Optionally, the dialkyl hypophosphite flame retardant is selected from diethyl aluminum hypophosphite.
[0015] The melamine derivative flame retardant is melamine polyphosphate.
[0016] In the GMA-grafted SEBS, the grafting rate of GMA is in the range of 0.2-1.5wt%, preferably 0.4-1.0wt%, and more preferably 0.6-0.8wt%.
[0017] GMA grafted SEBS can be a commercial product or can be obtained by self-production. The self-production method is as follows: dissolve dicumyl peroxide in GMA, then mix it with SEBS, and extrude it through a twin-screw extruder. The extrusion temperature is set at 200-220°C. Dissolve the extruded particles in toluene and heat them at about 100-120°C for 40-100 minutes. Cool to room temperature, add an appropriate amount of phenolphthalein, and titrate to the end point with a certain concentration of sodium hydroxide / methanol. After deducting the blank value, calculate the GMA content in the grafted product, and thus calculate the grafting rate.
[0018] Those skilled in the art can choose whether to add 0-2 parts of an auxiliary agent according to actual needs, wherein the auxiliary agent is selected from at least one of an antioxidant and a lubricant; and can choose whether to add 0-50 parts of glass fiber.
[0019] The antioxidant may be: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 2,5-di-tert-butyl-4-hydroxybenzyl dimethylamine; diethyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; stearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearyl-thiotriazolylamine; 2,6-di-tert-butyl-4-hydroxymethylphenol; 2,4-di-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylglycerol allyl ether)-1,3,5-triazine; N,N'-hexamethylenebis( 3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid); N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; triethylene glycol-bis[3-(3,5-dimethyl-4-hydroxyphenyl)propionate]; triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]; 2,2'-thiodiethyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc.
[0020] The lubricant may be: at least one of stearate lubricants, fatty acid lubricants, and stearate ester lubricants; the stearate lubricant is selected from at least one of calcium stearate, magnesium stearate, and zinc stearate; the fatty acid lubricant is selected from at least one of fatty acids, fatty acid derivatives, and fatty acid esters; the stearate ester lubricant is selected from at least one of pentaerythritol stearate.
[0021] The preparation method of the flame-retardant polyamide composite material of the present invention comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder to obtain the flame-retardant polyamide composite material, wherein the screw aspect ratio is 40-48:1, the barrel temperature is 220-270°C, and the screw speed is 200-450rpm.
[0022] The flame retardant polyamide composite material of the present invention is used for preparing electronic and electrical parts.
[0023] The present invention has the following beneficial effects: The present invention can toughen the material under the premise of ensuring V-0 flame retardancy by adding a certain amount of GMA grafted SEBS to the dialkyl hypophosphite flame retardant polyamide composite material. This is because in the flame retardant system of the present invention, MAH has a greater effect on the flame retardancy of the material than GMA grafting, and SEBS contains more benzene rings, which will also reduce the effect on the flame retardancy of the material. The amorphous PA6I / 6T has more benzene ring structures, which is conducive to improving flame retardancy and can also greatly improve the cantilever beam notched impact strength of the composite material.
[0024] At the same time, for crystalline polyamide materials, when more amorphous materials are added, on the one hand, its crystallization speed will be greatly affected, thus affecting the demoulding of the material. On the other hand, the molecular chains in the amorphous region are looser, which also has a certain weakening effect on flame retardancy. PA6I / 6T, because it has a certain benzene ring segment and a strong molecular chain rigidity, can avoid the problem of mold sticking and reduce the impact on the flame retardancy of the material. DETAILED DESCRIPTION
[0025] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0026] The sources of raw materials used in the present invention are as follows: PA6: PA66 EP-158, Zhejiang Huafeng Group; PA66: PA6 HY-2500A, Jiangsu Haiyang Chemical Fiber Co., Ltd.; PA6I / 6T-1: selar PA 3426, mass ratio of isophthalic acid to terephthalic acid is 7:3, dupont; PA6I / 6T-2: The mass ratio of isophthalic acid to terephthalic acid is 6.5:3.5, homemade; PA6I / 6T-3: The mass ratio of isophthalic acid to terephthalic acid is 7.5:2.5, homemade; PA6I / 6T-4: The mass ratio of isophthalic acid to terephthalic acid is 5.5:4.5, homemade; PA6I / 6T-5: The mass ratio of isophthalic acid to terephthalic acid is 8.5:1.5, homemade; PA6I / 6T can be a commercial product or can be obtained by self-production. The self-production method is as follows: a certain amount of terephthalic acid and hexamethylenediamine are mixed and 35-45% of deionized water is added, the molar ratio is 1:1.01~1.02, the temperature is adjusted to 45-55℃, the reaction is stirred for 1-3h, the pH value is adjusted to about 7.3~7.6, the reaction is continued for 1-3h, and a clear and transparent PA6T salt solution is obtained after the reaction is completed. After cooling, the solution is filtered and dried to obtain a white PA6T salt powder. The preparation process of PA6I salt is similar to the above steps. A fixed ratio of PA6I salt and PA6T salt are added to the reactor and mixed, and a certain amount of additives are added. After checking the air tightness, the mixture is replaced with nitrogen for more than 3 times and filled to a slight positive pressure of about 0.08-0.12 MPa. Stirring and heating are turned on, the temperature is raised to 140-160℃ and the reaction is carried out for 1-3h, and then the temperature is continued to be raised to 200-220℃ and the temperature is kept at a constant pressure for 3-6 h, the pressure is maintained at about 2.1-2.3 MPa, then the temperature is slowly raised to 300-320 ℃ within 2-4 h, and the pressure is gradually reduced to normal pressure. Finally, vacuum is applied, and the torque and current are observed. When the maximum value is reached, the stirring is stopped, nitrogen is filled in for back pressure, and the valve is opened to discharge the material to obtain PA6I / 6T.
[0027] PA MACM12: Grilamid TR90, EMS company; PA6I: KFHP51, Zhuhai Wantong Special Engineering Plastics Co., Ltd. PA6T: KFHP41, Zhuhai Wantong Special Engineering Plastics Co., Ltd. Diethylaluminum hypophosphite: Exolit OP 1230, Clariant; Melamine polyphosphate: Melapur 200 / 70, available from BASF SE; Toughening agent A: GMA grafted SEBS, GMA grafting rate is 1.0wt%, homemade; Toughening agent B: GMA grafted SEBS, GMA grafting rate 0.8wt%, homemade; Toughening agent C: GMA grafted SEBS, GMA grafting rate 0.6wt%, homemade; Toughening agent D: GMA grafted SEBS, GMA grafting rate 0.4wt%, homemade; Toughening agent E: GMA grafted SEBS, GMA grafting rate is about 0.8wt%, KT-35L, Shenyang Ketong; Toughening agent F: GMA grafted POE, KT-35, grafting rate 0.8%, Shenyang Ketong; Toughener G: MAH grafted SEBS, SEBS FG1901 GT, Kraton, USA; Toughener H: POE, POE 9061, ExxonMobil; Toughener I: ethylene-butyl acrylate copolymer, ELVALOY AC34035, purchased from DuPont, USA; Toughening agent J: SEBS, SEBS G1651, Kraton, USA; Glass fiber: Glass fiber ECS301CL-3, Chongqing International Composite Materials Co., Ltd.; Antioxidant: Irganox@ 1098, BASF; Preparation method of flame-retardant polyamide composite material of embodiment and comparative example: according to the ratio, each component is mixed evenly, and granulated by extrusion through a twin-screw extruder to obtain a flame-retardant polyamide composite material, the screw aspect ratio is 40-48:1, the barrel temperature is 220-270°C, and the screw speed is 200-450rpm.
[0028] Various test methods: (1) Flame retardant: 125×13×1.6 mm specimens were made by injection molding and tested according to UL 94 standard. At the same time, the time for the flame to go out during the test was recorded (the sum of the total burning time of 5 specimens twice).
[0029] (2) Izod notched impact strength: Injection molding ISO 180 standard specimens to test the Izod notched impact strength.
[0030] Table 1: Test results of each component of the flame retardant polyamide composite material of Examples 1-7 by weight Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PA6 20 35 25 25 25 25 PA66 25 PA6I / 6T-1 30 10 20 20 PA6I / 6T-2 20 PA6I / 6T-3 20 PA6I / 6T-4 20 Diethylaluminum hypophosphite 20 12 15 15 15 15 15 Melamine polyphosphate 1 5 3 3 3 3 3 Toughener A 0.5 2 1 1 1 1 1 Fiberglass 10 0 20 20 20 20 20 Antioxidants 0.5 0 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 V-0 Flame extinguishing time 33.6 35.4 35.3 31.3 30.2 34.6 42.4 <![CDATA[Notched impact strength kJ / m 2 > 7.5 5.8 9.8 9.7 9.5 9.4 9.1 It can be seen from Examples 3 / 5 / 6 / 7 / 8 that the flame extinguishing time is shorter in the combustion test when the preferred PA6I / 6T repeating unit content is used.
[0031] Table 2: Test results of each component of the flame retardant polyamide composite material of Examples 8-12 by weight Example 8 Example 9 Example 10 Embodiment 11 Example 12 PA6 25 25 25 25 25 PA6I / 6T-1 20 20 20 20 PA6I / 6T-5 20 Diethylaluminum hypophosphite 15 15 15 15 15 Melamine polyphosphate 3 3 3 3 3 Toughener A 1 Toughener B 1 Toughener C 1 Toughener D 1 Toughener E 1 Fiberglass 20 20 20 20 20 Antioxidants 0.5 0.5 0.5 0.5 0.5 Flame retardant V-0 V-0 V-0 V-0 V-0 Flame extinguishing time 39.6 33.1 32.4 37.2 32.8 <![CDATA[Notched impact strength kJ / m 2 > 9.3 9.6 9.3 9.1 9.7 It can be seen from Examples 3 / 9-12 that the preferred toughening agent with a maleic anhydride content has a shorter flame extinguishing time during the combustion test.
[0032] Table 3: Test results of each component by weight of the flame retardant polyamide composite materials of Comparative Examples 1-5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 PA6 25 25 35 25 25 PA6I / 6T-1 5 40 PA MACM12 20 PA6I 20 PA6T 20 Diethylaluminum hypophosphite 15 15 12 15 15 Melamine polyphosphate 3 3 5 3 3 Toughener A 1 1 2 1 1 Fiberglass 20 20 0 20 20 Antioxidants 0.5 0.5 0 0.5 0.5 Flame retardant V-1 V-1 * * V-1 Flame extinguishing time 72.5 56.2 * * 64.3 <![CDATA[Notched impact strength kJ / m 2 > 10.5 7.6 * Difficult to demould * Difficult to demould 6.8 It can be seen from Comparative Example 1 that although PA MACM12 is also a non-crystalline polyamide, it cannot achieve the effect of improving flame retardancy.
[0033] It can be seen from Comparative Example 2 that if the content of PA6I / 6T is too low, the flame retardancy cannot reach V-0.
[0034] It can be seen from Comparative Example 3 that if the content of PA6I / 6T is too high, demoulding will be difficult.
[0035] It can be seen from Comparative Example 4 that demoulding is difficult when crystallized PA6I is used instead of PA6I / 6T.
[0036] It can be seen from Comparative Example 5 that the flame retardancy is poor when crystallized PA6T is used instead of PA6I / 6T.
[0037] Table 4: Test results of each component by weight of the flame retardant polyamide composite material of Comparative Examples 6-10 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 PA6 25 25 25 25 25 PA6I / 6T-1 20 20 20 20 20 Diethylaluminum hypophosphite 15 15 15 15 15 Melamine polyphosphate 3 3 3 3 3 Toughener F 1 Toughener G 1 Toughening Agent H 1 Toughener I 1 Toughener J 1 Fiberglass 20 20 20 20 20 Antioxidants 0.5 0.5 0.5 0.5 0.5 Flame retardant V-1 V-1 V-1 V-1 V-1 Flame extinguishing time 62.7 54.6 60.2 58.1 55.6 <![CDATA[Notched impact strength kJ / m 2 > 9.1 10.1 10.3 8.3 7.2 It can be seen from Comparative Example 6 that GMA grafted POE cannot achieve V-0 when used in the flame retardant system of the present invention.
[0038] It can be seen from Comparative Example 7 that the maleic anhydride grafted toughening agent cannot achieve V-0 when used in the flame retardant system of the present invention.
[0039] It can be seen from Comparative Examples 8-10 that conventional POE, ethylene-butyl acrylate copolymer, and SEBS cannot achieve V-0 flame retardancy.
[0040] It can be seen from the above examples and comparative examples that the flame retardant polyamide composite material of the present invention has a flame retardancy of V-0, a flame extinguishing time of <45s, and a notched impact strength of >5 kJ / m 2 .
Claims
1. A flame retardant polyamide composite material, characterized in that: By weight, it includes the following components: 20-35 parts of crystalline polyamide; PA6I / 6T 10-30 parts; 12-20 parts of dialkyl hypophosphite flame retardant; 1-5 parts of melamine derivative flame retardant; GMA grafted SEBS 0.5-2 parts.
2. The flame retardant polyamide composite material according to claim 1, characterized in that: In the PA6I / 6T, the mass ratio of isophthalic acid to terephthalic acid is (6.5-7.5): (3.5-2.5).
3. The flame retardant polyamide composite material according to claim 1, characterized in that: The crystalline polyamide is at least one of aliphatic polyamide and polylactam.
4. The flame retardant polyamide composite material according to claim 1, characterized in that: The structural formula of the dialkyl hypophosphite flame retardant is as follows: Among them, R 1 , R 2 Independently selected from linear or branched C1-C6 alkyl and / or aryl groups; M is selected from one or more combinations of alkali metals, alkaline earth metals, Al, Zn, Fe or Ti; m is 1-4.
5. The flame retardant polyamide composite material according to claim 4, characterized in that: The dialkyl hypophosphite flame retardant is selected from diethyl aluminum hypophosphite.
6. The flame retardant polyamide composite material according to claim 1, characterized in that: The melamine derivative flame retardant is melamine polyphosphate.
7. The flame retardant polyamide composite material according to claim 1, characterized in that: In the GMA-grafted SEBS, the grafting rate of GMA is in the range of 0.4-1.0wt%, preferably 0.6-0.8wt%.
8. The flame retardant polyamide composite material according to claim 1, characterized in that: By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of antioxidants and lubricants; and by weight, the invention further comprises 0-50 parts of glass fibers.
9. The method for preparing the flame retardant polyamide composite material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder to obtain a flame-retardant polyamide composite material, wherein the screw aspect ratio is 40-48:1, the barrel temperature is 220-270°C, and the screw speed is 200-450rpm.
10. Use of the flame retardant polyamide composite material according to any one of claims 1 to 8, characterized in that: Used to prepare electronic and electrical parts.
Citation Information
Patent Citations
High-weather-resistance UL94-5VA-grade flame-retardant reinforced polyamide composite material and preparation method thereof
CN110408200A
Flame-retardant bio-based polyamide material and preparation method thereof
CN111117225A
Halogen-free flame-retardant polyamide composition with good toughness as well as preparation and application thereof
CN115449217A
Cited By
Flame-retardant polyamide composite material, preparation method therefor and use thereof
WO2026118901A1